Trashumancia, Espacio para Poesía y Arte : enero-febrero 1993 - Ocaranza, Jorge Octavio (dirección); Gutiérrez Ramírez, Alfredo (edición) (Trashumancia, 1993)
Contiene obra de: Jorge Octavio Ocaranza, José Antonio Ramos Sucre, José Javier Coz, José Balza, Bernardo Esquinca, Ricardo Chávez Castañeda, Rolando Revagliatti, Ignacio Padilla, Carlos Aceves Azcárate, Horacio Castro de Bernardi, Enrique Blanc, Henri Michaux, Juan Bañuelos, Ana Aridjis, Antonio Alberto Guerrero, Arnulfo Sepúlveda, Carmen Nozal, David García Ruiz, Gloria Pérez, Héctor Guzmán Gutiérrez, Kato Molinari, José Guadalupe Ramírez, Marcos Davison, Níger Madrigal y Oscar Tagle.